Enhancing Autonomy in Preschoolers: The Role of Motor Games in Development - Gomes, Sara (2024)
This paper is based on a project which aims to understand the contribution of motricity—in particular, motor games—to the development of autonomy in preschool children, with or without special education needs. A group of 18 children, with an average age of 4.5 years, from a public school took part in the study. An intervention program based on motor games was implemented and tested to promote the children’s autonomy. The program lasted two months, with one 45-min session per week. Using a questionnaire designed for this purpose, the children’s autonomy was assessed pre- and post-intervention. The children’s satisfaction with the sessions was assessed throughout the intervention. The main results were improvements in the autonomy of all the children and their high satisfaction with the program. The participation of children, with and without specific needs, in the entire program shows the use of differentiated practices that allowed everyone to be included in this process.